CARDIOVASCULAR RISK FACTORS AND PRESCRIPTION PATTERN AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS IN NORTH-EAST NIGERIA - AGADA DAVID, EMMANUEL; SOREMEKUN, REBECCA O.; KATAGUM , YAHAYA M.; ADEREMI-WILLIAMS, ROSELINE I. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Cardiovascular disesaes are the leading cause of morbidity and mortality among diabetic patients. This study was a 12-months retrospective cross sectional audit of case folders of adult (>18 years) type 2 diabetic patients, who attended clinic at two (2) referral hospitals in North-East Nigeria, between June 2017 and May 2018. Patients’ data including socio-demographic characteristics, cardiovascular risk factors, medication history and clinical characteristics were retrieved. The data were presented as proportions and percentages in tables and pie chart formats. The analysis was done using statistical package for social sciences (SPSS) version 21.0. Of the 807 case folders that were reviewed, 64.5% were female patients, with majority (61.3%) below 50 years of age and 90.2% were married. Over 50% had secondary/primary education and most (57.9%) were unskilled labourers. About one-third (34.6%) were engaged in moderate to regular physical activities. The prevalence of hypertension, dyslipidaemia and obesity was 84.8%, 5.1% and 47.1% respectively. More than three quarters of the patients (87%) were on multiple oral antidiabetic agents and metformin was the most prescribed medication (93.8%). The antihypertensive agents with the highest prescription rate was lisinopril (57.9%), while 50.9%, 6.5%, and 2.7% received low dose acetylsalicylic acid, lipid lowering agents and pregabalin respectively. Hypertension was the most prevalent cardiovascular risk factor in the study population, followed by overweight/obesity. The prescription rate of metformin and Lisinopril is commendable, but there is need to increase the use of statins and pregabalin in the study settings.